Disseminating public data as public use files: what makes a successful initiative? - Prada, Sergio I.; Martinez, Lina (2018)
The current policy emphasis on data-driven decision-making is creating the right incentives for government agencies around the world that have not traditionally disseminated their administrative data to do so. The literature on statistical disclosure control focuses on the technical aspects of a variety of methods designed to protect data confidentiality. There is, however, a void in the literature in regard to what other elements are necessary to create and sustain a successful initiative. This paper examines six case studies of individual-level datasets. It reviews current practice in several domains and summarizes recommendations from expert practitioners including challenges for future initiatives. - Reproduced.
Keywords: Data protection; Datasets; Open data; Secrecy in government; Transparencies